Efectos de la meditaciÃ³n sobre el estrÃ©s acadÃ©mico en estudiantes de Licenciatura en Fisioterapia - GÃ³mez, Nancy Elizet GutiÃ©rrez; Cabrera, JosuÃ© Mauricio Becerra; Camacho, Miguel Ãngel MartÃnez; GutiÃ©rrez, MarÃa Carlota GarcÃa (European Scientific Journal, ESJ, 2017)
Introduction: Stress is one of the most common psychological disorders. In Mexico, a study of academic stress in college students found that a high percentage of students had experienced intense anxiety (73.4%). Research on physical therapy students at the Riphah Rehabilitation Science Center show that the prevalence of perceived stress is 88%.Meditation programs in college students had resulted beneficial for the management of stress, depression and anxiety. Objective: To determine the effects of meditation on academic stress in first semester students of the degree in physiotherapy of the Autonomous University of QuerÃ©taro. Methodology: Quasi-experimental study. Participants: Thirty-six firstsemester students of the physiotherapy degree from the Autonomous University of QuerÃ©taro, a control group of 17 students and 19 in the experimental group. The experimental group was intervened for 8 weeks with guided meditation sessions with duration of 20 to 25 minutes from Monday to Friday. Both control and experimental groups were evaluated through the Academic Stress Inventory before and after the intervention program. Results: There is a significant reduction in stress levels using meditation in the experimental group (p = 0.0002). For the control group, no significant difference was found in stress p = 0.093. Conclusion: An 8-week meditation program has healthy effects on the academic stress of undergraduate physical therapy students.